Conservative management of odontogenic keratocyst with long-term 5-year follow-up: Case report and literature review - Vallejo-Rosero, Kleber A. (Int J Surg Case Rep, 2019)
INTRODUCTION: Odontogenic Keratocyst (OKC) is a benign lesion recently considered an odontogenic cyst in the present World Health Organization (WHO) classification of Head and Neck tumors (2017) mainly based on its clinical and histopathological features. Several studies, systematic reviews and meta-analyses have shown a multimodal approach to reducing the high recurrence rates inherently exhibited by this pathological condition after long-term periods of follow-up. PRESENTATION OF CASE: The patient, a 67-years-old woman, was submitted to conservative surgical management of an odontogenic keratocyst. Initially this consisted of decompression and subsequent enucleation, with a long-term period of follow-up to ensure that there was no recurrence. DISCUSSION: Conservative surgical management is the first choice and might be considered the gold standard, but combined therapy such as marsupialization, application of Carnoy’s solution, enucleation of the remnant lesion and an extensive follow-up period would considerably reduce recurrence rates. CONCLUSION: Therefore, an appropriate long-term follow-up must be done after the treatment performed in order to ensure clinical success, which in this case was described as an absence of signs of recurrent disease.